SIFO 1988: If the Green Party enters the Parliament - Swedish Institute of Public Opinion Research; Veckans Affärer (business magazine) (Swedish Institute of Public Opinion Research, 1993)
In this study carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of the business magazine Veckans Affärer, the respondent was asked questions about which political party had the best ideas for solving the environmental problems, and the importance of environmental issues when deciding which political party to vote for in the general election. The respondent also had to give an opinion on how much of their party program the Green Party would be able to accomplish if they entered the parliament, and if she/he ever considered voting on the Green Party in the 1988 election. Background variables include information on gender, place of living, age, Swedish citizenship, occupation, private or public sector, trade union, right to vote in general elections, voting habit, political party preference and party voted for in 1985.

Studien har genomförts av SIFO (Svenska institutet för opinionsundersökningar) på uppdrag av tidningen Veckans Affärer 1988. Materialet består av information om vilket politiskt parti respondenterna ansåg hade de bästa idéerna för att lösa miljöproblemen och vikten av miljöfrågor vid val av parti att rösta på till riksdagsvalet. Innehåller även frågor om Miljöpartiets förmåga att förverkliga sitt partiprogram vid en eventuell plats i riksdagen, om respondenten tänkt rösta på Miljöpartiet i valet 1988 samt flertalet bakgrundsvariabler som exempelvis kön, ålder, partisympati, yrke och vana av att rösta.
SIFO 1988: Om miljöpartiet kommer in i riksdagen
Keywords: Environment and conservation; Miljö och naturvård; Elections; Val; Social Sciences; Samhällsvetenskap